Chapter 1 Alloy Steel: Properties and Use First-Principles Quantum Mechanical Approach to Stainless Steel Alloys - Al-Zoubi, N. (InTechOpen, 2011)
Accurate description of materials requires the most advanced atomic-scale techniques from both experimental and theoretical areas. In spite of the vast number of available techniques, however, the experimental study of the atomic-scale properties and phenomena even in simple solids is rather difficult. In steels the challenges become more complex due to the interplay between the structural, chemical and magnetic effects. On the other hand, advanced computational methods based on density functional theory ensure a proper platform for studying the fundamental properties of steel materials from first-principles. In 1980's the first-principles description of the thermodynamic properties of elemental iron was still on the borderline of atomistic simulations. Today the numerous application- oriented activities at the industrial and academic sectors are paired by a rapidly increasing scientific interest. This is reflected by the number of publications on ab initio steel research, which has increased from null to about one thousand within the last two decades. Our research group has a well established position in developing and applying computational codes for steel related applications. Using our ab initio tools, we have presented an insight to the electronic and magnetic structure, and micromechanical properties of austenite and ferrite stainless steel alloys. In the present contribution, we review the most important developments within the ab initio quantum mechanics aided steel design with special emphasis on the role of magnetism on the fundamental properties of alloy steels.